Optimizing Cost Control in the Hospitality Sector: A Comprehensive Study of Food and Beverage Management: Optimalisasi Pengendalian Biaya di Sektor Perhotelan: Studi Komprehensif Manajemen Makanan dan Minuman - Nasir, Muh Ersyad; Gunawan, Indra (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study investigates cost control strategies within the food and beverage sector of Aston Makassar Hotel & Convention Center, addressing the challenges posed by fluctuating raw material prices and supplier reliance. Utilizing a mixed-methods approach, data were collected through surveys of kitchen staff and in-depth interviews with the Executive Chef. The findings reveal significant cost management issues, particularly related to supplier selection and consistency in product quality, which directly affect profitability and customer satisfaction. Notably, events such as weddings led to peaks in expenditures, highlighting the need for strategic planning in resource allocation. The study concludes that effective cost control measures are essential for enhancing operational efficiency and guest experiences. By identifying specific cost drivers and implementing best practices, hotels can better navigate economic uncertainties and maintain competitive advantage in the hospitality industry. Recommendations for improving cost management strategies are presented, aiming to support sustainable growth and customer loyalty